Non-Commercial Advertisements: Multimodal Metaphor, Metonymy and Conceptual Blending at Work - Ikere, Zaiga; Oļehnoviča, Ilze; Liepa, Solveiga (Research in Language, 2021)
Nowadays the omnipresence of advertisements, and the necessity of conscious and subconscious mental interpretation of their hidden messages, can hardly be overlooked. In the present article, the authors attempt to provide additional evidence for the role of multimodal metaphor, metonymy, and conceptual blending in hidden cognitive mechanisms involved in the understanding and/or the correct interpretation of printed non-commercial advertisements and their overall communicative effect thus brought about. The objective is to consider and analyse text-image non-commercial advertisements randomly retrieved from the Internet; the analysis is carried out from the cognitive perspective and aims at discussing the functions of multimodal metaphor, metonymy and conceptual blending as powerful mechanisms exploited for creative purposes in advertising texts and accompanying images, and thus in conveying the central ideas embedded in the adverts.